An empirical analysis of corporate legitimacy through corporate responsibility activities among government-linked companies (GLCs): the influences of special interest groups / Mahadir Ladisma @ Awis - Ladisma@Awis, Mahadir (2016)
Corporate social responsibility (CSR) is one of the new corporate governance mantras that give some credence to stakeholder theory of corporations. Studies have examined the interest in, levels and effects of CSR investments on employees, customers, investors etc. However, CSR is an intermediate outcome. Corporate legitimacy is what corporations seek to achieve through CSR although this is not always explicit. This study examines the relationship between corporate responsibility and corporate legitimacy. Secondly, corporate responsibility intensity and types of corporate responsibility activities have been examined from the standpoint of shareholders, customers, employees and other groups closely linked to the businesses. These are undoubtedly sections of society but they are role restricted groups. This study examines the less role restricted special interest groups (SIGs) that represent and/or speak on behalf of the various components of the society. The study focused on 17 publicly listed Government Linked Corporations (GLCs) which are pressured by their owner - the government, to be socially sensitive and responsible in their business activities. The three main aims of the study are: (i) to determine the level of corporate legitimacy perceptions of GLCs in the eyes of SIGs as proxies for society (special interest groups); (ii) to examine whether and which type of corporate responsibility activities of GLCs influence their corporate legitimacy perceptions; and (iii) to find out the extent to which the SIGs characteristics moderate the relationship between corporate responsibility activities and corporate legitimacy of GLCs. 17 research hypotheses were developed and tested to examine the relationship between three dimensions of corporate responsibility activities - philanthropy related, business related and product related and corporate legitimacy with three SIG characteristics (size, age and access factor) as moderators. The study employed a cross-sectional sample survey designed to collect data from a pre-selected list of SIGs obtained from the Registrar of Societies, Malaysia. From a list of about 22,119 societies, 377 were shortlisted covering six categories of societies. Partial Least Square-Structural Equation modelling (PLS-SEM) was used to analyse the data collected from a sample of 266 SIGs in Malaysia. The empirical results indicate that corporate responsibility activities significantly influence the corporate legitimacy perceptions of GLCs by the SIGs. This study also found that there is a positive relationship between two of the three components of corporate responsibility activities of GLCs: philanthropy and business practices-related and corporate legitimacy. However, there was no support for the hypothesis that SIG's characteristics moderate the relationship between corporate responsibility activities and corporate legitimacy. The study expands the remit of traditional CSR studies to truly venture into the societal components which are not directly dependent on the businesses in questions. Customer, employees and investors are important direct stakeholders in the businesses. Studying the SIG's perceptions expands the boundaries of the CSR investigations. Secondly, returning to the latent but the eventual outcomes of corporate responsibility, links corporate responsibility to its precursor or predecessor construct - corporate legitimacy. The relationship of corporate responsibility to corporate legitimacy is in focus in this study. These two lines of investigations make important contribution to the theory and practice of CSR.